Spatiotemporal observation of light propagation in a three-dimensional scattering medium - Tomoyoshi Inoue (Nature Portfolio, 2021)
Abstract Spatiotemporal information about light pulse propagation obtained with femtosecond temporal resolution plays an important role in understanding transient phenomena and light–matter interactions. Although ultrafast optical imaging techniques have been developed, it is still difficult to capture light pulse propagation spatiotemporally. Furthermore, imaging through a three-dimensional (3-D) scattering medium is a longstanding challenge due to the optical scattering caused by the interaction between light pulse and a 3-D scattering medium. Here, we propose a technique for ultrafast optical imaging of light pulses propagating inside a 3D scattering medium. We record an image of the light pulse propagation using the ultrashort light pulse even when the interaction between light pulse and a 3-D scattering medium causes the optical scattering. We demonstrated our proposed technique by recording converging, refracted, and diffracted propagating light for 59 ps with femtosecond temporal resolution.